DIGITAL CONTENT MARKETING FOR ENVIRONMENTAL AWARENESS: EFFECTIVENESS OF SOCIAL MEDIA CAMPAIGNS IN PROMOTING GREEN CONSUMERISM - Dixian Bhikuning; Dara Kusumawati; Dison Librado (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
Digital transformation has changed the landscape of environmental communication, where social media has become an important instrument in shaping people's ecological awareness. This study explores the effectiveness of digital content marketing campaigns in encouraging environmental awareness and green consumption behavior in Indonesia. The research uses a descriptive qualitative approach with a content analysis method on digital campaigns conducted by environmental organizations such as Greenpeace Indonesia, Zero Waste Indonesia, as well as various local eco-friendly brands on TikTok, Instagram, and YouTube platforms for the period January 2023 to December 2024. The findings show that content strategies that integrate educational, emotional, and actionable approaches result in significant audience engagement rates, with short video content achieving an engagement rate of 8-12%. Campaigns that successfully build emotional connections and provide practical solutions have proven to be more effective in turning awareness into sustainable consumption actions. Ecological and environmental awareness plays an important role as an important mediator in the adoption of green practices. This research makes a theoretical contribution to the development of sustainable digital marketing literature and practically serves as a guide for practitioners in designing more effective digital campaigns to drive the transformation of consumer behavior towards sustainability.